Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

The work of a student to solve the equation 2(3x − 4) = 8 + 2x + 4 is shown below:

Step 1: 2(3x − 4) = 8 + 2x + 4
Step 2: 5x − 6 = 12 + 2x
Step 3: 5x − 2x = 12 + 6
Step 4: 3x = 18
Step 5: x = 6

In which step did the student first make an error and what is the correct step?

Step 2; 6x − 6 = 2(6 + x + 2)
Step 2; 6x − 8 = 12 + 2x
Step 3; 5x − 2x = 12 − 6
Step 3; 5x + 2x = 12 + 6


Sagot :

Answer:

answer is x=5, not x=6

Step-by-step explanation:

I don't really understand how this is structured, but the correct way of solving this is

2(3x − 4) = 8 + 2x + 4

do distributive property.

6x - 8 =  8 + 2x + 4

subtract 2x on both sides.

you get...

4x - 8 = 12

add 8 on both sides.

4x =20

divide by 4

x = 5

We hope this was helpful. Please come back whenever you need more information or answers to your queries. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.